2021
DOI: 10.3390/e23091168
|View full text |Cite
|
Sign up to set email alerts
|

Consideration for Affects of an XOR in a Random Number Generator Using Ring Oscillators

Abstract: A cloud service to offer entropy has been paid much attention to. As one of the entropy sources, a physical random number generator is used as a true random number generator, relying on its irreproducibility. This paper focuses on a physical random number generator using a field-programmable gate array as an entropy source by employing ring oscillator circuits as a representative true random number generator. This paper investigates the effects of an XOR gate in the oscillation circuit by observing the output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this context, the authors introduce the transition probability by considering the Markov process for an RO-based generator from previous research [ 14 ]. It is noted that the readers can refer to [ 4 ], as a work related to this paper.…”
Section: A Test Methods and Evaluation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the authors introduce the transition probability by considering the Markov process for an RO-based generator from previous research [ 14 ]. It is noted that the readers can refer to [ 4 ], as a work related to this paper.…”
Section: A Test Methods and Evaluation Processmentioning
confidence: 99%
“…In a previous work [ 14 ], the authors discussed the importance of an XOR gate in a generator based on ROs by approximating the periodicity and investigating the transition probabilities of 2-bit patterns. It was revealed that an XOR gate in an RO-based generator contributes to extending the period length, and the number of ROs is of relevance to the distribution property.…”
Section: Preliminariesmentioning
confidence: 99%